1985
DOI: 10.1139/z85-441
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate differentiation of parapatric and allopatric populations of threespine stickleback in the Sangan River watershed, Queen Charlotte Islands

Abstract: A discriminant analysis was made of 17 morphometric and 10 meristic characters in the freshwater form (leiurus) of threespine stickleback (Gasterosteus aculeatus) from 16 localities in the Sangan River System on the Queen Charlotte archipelago and in the presumed ancestral form (trachurus) from a nearby locality in marine waters. While multivariate means were significantly different between trachurus and leiurus, there was even greater differentiation between the leiurus populations found in lakes, ponds, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
187
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(220 citation statements)
references
References 20 publications
19
187
1
3
Order By: Relevance
“…Both of the large-effect gill raker QTL had regionally specific effects, the QTL on right chromosome 4 controlling anterior ventral gill raker number and spacing and the chromosome 20 raker QTL controlling strictly ventral gill raker number (Figure 4 and Figure S2). This decoupling of the genetic control of dorsal and ventral gill rakers is also consistent with a previous ecological study that found ventral, but not dorsal, gill raker number to have predictive value in discriminating different wild freshwater populations, perhaps reflecting population-specific diets (Reimchen et al 1985). The anatomical specificity of QTL might be even more complex; even within the ventral domain, the chromosome 20 raker QTL had regional effects, controlling only lateral and middle, but not medial spacing ( Figure S2).…”
Section: Regional Control Of Skeletal Anatomysupporting
confidence: 90%
“…Both of the large-effect gill raker QTL had regionally specific effects, the QTL on right chromosome 4 controlling anterior ventral gill raker number and spacing and the chromosome 20 raker QTL controlling strictly ventral gill raker number (Figure 4 and Figure S2). This decoupling of the genetic control of dorsal and ventral gill rakers is also consistent with a previous ecological study that found ventral, but not dorsal, gill raker number to have predictive value in discriminating different wild freshwater populations, perhaps reflecting population-specific diets (Reimchen et al 1985). The anatomical specificity of QTL might be even more complex; even within the ventral domain, the chromosome 20 raker QTL had regional effects, controlling only lateral and middle, but not medial spacing ( Figure S2).…”
Section: Regional Control Of Skeletal Anatomysupporting
confidence: 90%
“…Therefore, transformation of absolute measurements to size-independent shape characters was performed before the final analysis. In order to eliminate any variation resulting from allometric growth, all morphometric characters were therefore adjusted to an overall mean standard length of 12.63 cm according to the following equation (Reimchen et al, 1985;Senar et al, 1994):…”
Section: Discussionmentioning
confidence: 99%
“…In the present paper, we empirically investigate whether adaptive divergence represents a compromise between selection and gene flow for conspecific fish populations that reside in adjacent lakes and streams. Adaptive divergence between these environments has been documented for threespine stickleback (Gasterosteus aculeatus; Moodie 1972a,b;Reimchen et al 1985;Lavin and McPhail 1993), juvenile coho salmon (Oncorhynchus kisutch; Swain and Holtby 1989), adult anadromous sockeye salmon (Oncorhynchus nerka; Hendry et al 2000), and adult nonanadromous kokanee (Oncorhynchus nerka; Taylor et al 1997). Lake and stream population pairs obviously experience divergent selection but, because of their proximity, they may also exchange many migrants (e.g., Hendry et al 2000).…”
mentioning
confidence: 99%
“…Parapatric lake and stream stickleback have been described for three systems in British Columbia: Drizzle and Mayer Lakes on the Queen Charlotte Islands (Moodie 1972a,b;Reimchen et al 1985) and Misty Lake on Vancouver Island (Lavin and McPhail 1993;Thompson et al 1997). In each case, stream-dwelling fish have deeper bodies for their length (i.e., less streamlined) and fewer gill rakers.…”
mentioning
confidence: 99%
See 1 more Smart Citation